Intermittent Normal Ventricular Conduction in Left Bundle Branch Block After TAVR - Edoardo Cecchini, MD; Gianluca Massaro, MD; Vincenzo Carbone, MD; Giuseppe Sangiorgi, MD (JACC: Case Reports, 2023)
In a patient who previously developed left bundle branch block after transcatheter aortic valve replacement, intermittent narrow QRS complexes were recorded on ambulatory electrocardiography monitoring. The peculiar distribution of wide and narrow QRS complexes suggested the presence of a window of supernormality in the refractory period of a branch block that on other occasions exhibited the Wenckebach phenomenon. (Level of Difficulty: Intermediate.)